2018
DOI: 10.5194/acp-18-5515-2018
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic constraints on heterogeneous sulfate production in Beijing haze

Abstract: Abstract. Discerning mechanisms of sulfate formation during fine-particle pollution (referred to as haze hereafter) in Beijing is important for understanding the rapid evolution of haze and for developing cost-effective air pollution mitigation strategies. Here we present observations of the oxygen-17 excess of PM 2.5 sulfate ( 17 O(SO 2− 4 )) collected in Beijing haze from October 2014 to January 2015 to constrain possible sulfate formation pathways. Throughout the sampling campaign, the 12-hourly averaged PM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
127
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 61 publications
15
127
3
Order By: Relevance
“…This is supported by the eNO z and eHNO 3 values, which increased from 0.07 and 0.03 at 1:00 LT on 3 December to 0.21 and 0.09 at LT 5:00 on 4 December (Figure d) during the nighttime, respectively. This is also consistent with that reported by He et al (), who used the oxygen isotope methods to find the importance of nocturnal chemistry in nitrate production in Beijing haze.…”
Section: Resultssupporting
confidence: 92%
“…This is supported by the eNO z and eHNO 3 values, which increased from 0.07 and 0.03 at 1:00 LT on 3 December to 0.21 and 0.09 at LT 5:00 on 4 December (Figure d) during the nighttime, respectively. This is also consistent with that reported by He et al (), who used the oxygen isotope methods to find the importance of nocturnal chemistry in nitrate production in Beijing haze.…”
Section: Resultssupporting
confidence: 92%
“…where NH + 4 , Na + , K + , Ca 2+ , Mg 2+ , SO 2− 4 , NO − 3 , and Cl − are the mass concentrations (µg m −3 ) of these ions in the atmosphere; [cations] and [anions] denote the sum of charge-equivalent total molar concentrations (µmol m −3 ) of cations and anions, respectively. Although they are straightforward to calculate, a few recent studies (Hennigan et al, 2015;Guo et al, 2016;Murphy et al, 2017) have demonstrated that the ion balance and equivalent ratio calculated from ambient particle measurements should not be used to predict the acidity of particles, especially under ammonia-rich conditions, for several reasons summarized as follows. (1) This would require all ions other than H + and OH − to be measured with both very high accuracy and precision, conditions unlikely to be achieved in practice.…”
Section: Ph Prediction By Thermodynamic Modelsmentioning
confidence: 99%
“…In spite of its significance, ambient particle pH is still poorly constrained. The direct filter sampling approach is challenged by the nature of hydrogen ions in that its concentration in a solution does not scale in proportion to the level of dilution, and it is also subject to sampling errors (Hennigan et al, 2015). A few studies have determined the pH of laboratory-generated particles using colorimetry/spectrometry and Raman microspectroscopy (Li and Jang, 2012;Rindelaub et al, 2016;Craig et al, 2017), but such techniques have not been applied to ambient particles, partly due to their much more complex chemical and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…) and high RH while photochemistry is often less active (Wang et al, 2016b;Cheng et al, 2016b). Field observations, chamber experiments, source apportionments and simulation works all suggests that the joint effect of NO2, SO2, and NH3 is important in the sulfate formation processes in haze events (Cheng et al, 2016b;Wang et al, 2016b;He et al, 2018).Aqueous oxidation of SO2 by NO2 could be of major process of sulfate 55 formation in winter Beijing, as well as transition metal ions (TMI) catalyzed oxidation (Wang et al, 2016b;Cheng et al, 2016b). Besides, though the photochemistry were less active during winter haze periods, extra radical provided by HONO might enhance the atmospheric oxidation capacity and thus leads to extra SNA formation (Tan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%